Association Between Awareness of Hypertension and Health-Related Quality of Life in a Cross-Sectional Population-Based Study in Rural Area of Northwest China. Issue 29 (July 2015) - Mi, Baibing; Dang, Shaonong; Li, Qiang; Zhao, Yaling; Yang, Ruihai; Wang, Duolao; Yan, Hong; Jose, Vilela-Martin.
<x xml:space="preserve">Abstract</x> Abstract Hypertensive patients have more complex health care needs and are more likely to have poorer health-related quality of life than normotensive people. The awareness of hypertension could be related to reduce health-related quality of life. We propose the use of quantile regression to explore more detailed relationships between awareness of hypertension and health-related quality of life. In a cross-sectional, population-based study, 2737 participants (including 1035 hypertensive patients and 1702 normotensive participants) completed the Short-Form Health Survey. A quantile regression model was employed to investigate the association of physical component summary scores and mental component summary scores with awareness of hypertension and to evaluate the associated factors. Patients who were aware of hypertension (N = 554) had lower scores than patients who were unaware of hypertension (N = 481). The median (IQR) of physical component summary scores: 48.20 (13.88) versus 53.27 (10.79), P < 0.01; the mental component summary scores: 50.68 (15.09) versus 51.70 (10.65), P = 0.03. adjusting for covariates, the quantile regression results suggest awareness of hypertension was associated with most physical component summary scores quantiles (P < 0.05 except 10th and 20th quantiles) in which the β-estimates from −2.14 (95% CI: −3.80 to −0.48) to −1.45 (95% CI: −2.42 to −0.47), as the same significant trend with some poorer mental component summary scores quantiles in which the β-estimates from −3.47 (95% CI: −6.65 to −0.39) to −2.18 (95% CI: −4.30 to −0.06). The awareness of hypertension has a greater effect on those with intermediate physical component summary status: the β-estimates were equal to −2.04 (95% CI: −3.51 to −0.57, P < 0.05) at the 40th and decreased further to −1.45 (95% CI: −2.42 to −0.47, P < 0.01) at the 90th quantile. Awareness of hypertension was negatively related to health-related quality of life in hypertensive patients in rural western China, which has a greater effect on mental component summary scores with the poorer status and on physical component summary scores with the intermediate status.